Pengaruh Pemberian Terapi Akupresur terhadap Tekanan Darah Lansia di Puskesmas Kediri I Tabanan - Ni Made Suwarini; Ni Made Ari Sukmandari; Made Ririn Sri Wulandari (Jurnal Surya Medika (JSM), 2021)
Long as the elderly are getting older, the cardiovascular system will experience changes such as arteries losing their elasticity, leading to an increase in pulse and systolic blood pressure. Acupressure is a development of acupuncture therapy that can lower blood pressure; stimulation at the acupressure point causes the release of endorphin hormones which reduce lactic acid production to provide a relaxed and comfortable condition. This study used a pre-experimental research design with a one-group pre-posttest design with simple random sampling, which involved 34 elderly with hypertension. According to the standard operational procedure (SOP), blood pressure was measured with a sphygmomanometer, and acupressure therapy was the standard operational procedure (SOP). Data analysis was carried out using a paired t-test because the data were normally distributed. The results showed that the mean blood pressure before the intervention was 152.35/97.65 mmHg, while after the intervention, the average blood pressure was 140.74/90.59 mmHg. Analysis with paired sample t-test obtained p-value = 0.001 in systolic and diastolic pressures. There were differences in blood pressure before and after acupressure therapy intervention in the elderly at Kediri I Public Health Center, Tabanan Regency. It is hoped that nurses can independently provide acupressure therapy to older adults with hypertension to lower blood pressure.